Teachers' perceptions of student understanding in the science classroom. - Gibson, Adrienne T. (Curtin University, 2003)
In the USA, science teachers are challenged by the National Science Education Standards (NSES) to "select teaching and assessment strategies that support the development of student understanding and nurture a community of science learners" (NRC, 1996, p. 30). While standards do not explicitly refer to constructivist learning theory, they are entirely consistent with the view that knowledge is a human construction, learning is based on prior knowledge, and students respond to their environment to build new understandings. Paralleling the NSES reforms, with their constructivist underpinnings, there is also a strong and often contradictory pressure on teachers to prepare students for national and state standardised tests. The need for teachers to balance these competing demands while trying to teach for understanding sets the context for this research.The purpose of this research has been to focus on "how" teachers determine students' understanding and "why" they employ the instructional and assessment strategies that they do. Interpretive case studies of five teacher participants from one school district are used to describe how these teachers teach for understanding in the face of the competing pressures of conforming to the NSES and preparing students for success on standardised multiple-choice achievement tests. These case studies are analysed to identify common themes and propositions about teaching for understanding.The teachers in this study used a variety of instructional and assessment strategies. Their choices of strategies made a difference in the degree of understanding that their students achieved. Frequently, the teachers' decisions were affected by their grasp of science concepts and ideas about how students learned. When teaching for understanding, these teachers preferred informal knowledge of student understanding to that obtained from standardised tests Although subjected to conflicting pressures regarding how teachers were able to disregard assessments that did not provide evidence of student understanding. This research has implications for the five teacher participants, myself as a researcher, the district as a whole and educators with an interest in implementing assessment strategies that foster student achievement for understanding.